2008
DOI: 10.2746/095777308x329163
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study comparing conservative and surgical treatments of open comminuted fractures of the fourth metatarsal bone in horses

Abstract: Summary The proximal third of metatarsal IV is predisposed to open comminuted fractures due to its superficial and prominent position and controversy exists regarding the most appropriate management for this type of fracture. Fifty‐three horses treated for open comminuted fractures of the proximal third of metatarsal IV were selected for study from 6 equine hospitals across England. Comparisons were made between the 21 horses treated conservatively and the 32 horses treated surgically. Horses treated conservat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 11 publications
0
29
0
Order By: Relevance
“…Another study suggested that conservative therapy of open comminuted fractures of the proximal one-third of MT4 had comparable rates of survival, return to full work and convalescent period to those of surgically managed patients. 24 In that study, 80% of the horses were acutely injured (< 3 weeks since the injury) and conservative management offered a better prognosis. They also reported that horses that did not respond to conservative therapy developed exuberant callus formation, which led to longer convalescence times.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…Another study suggested that conservative therapy of open comminuted fractures of the proximal one-third of MT4 had comparable rates of survival, return to full work and convalescent period to those of surgically managed patients. 24 In that study, 80% of the horses were acutely injured (< 3 weeks since the injury) and conservative management offered a better prognosis. They also reported that horses that did not respond to conservative therapy developed exuberant callus formation, which led to longer convalescence times.…”
Section: Discussionmentioning
confidence: 91%
“…In the current series, most of the included subjects had undergone conservative therapy for 3–5 months without improvement and thus surgical intervention was the alternative option. Another study suggested that conservative therapy of open comminuted fractures of the proximal one‐third of MT4 had comparable rates of survival, return to full work and convalescent period to those of surgically managed patients . In that study, 80% of the horses were acutely injured (< 3 weeks since the injury) and conservative management offered a better prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations